Aneurysm treatment in Europe 2010: an internet survey - Bradac, Ondrej; Hide, Susie; Mendelow, David A; Benes, Vladimir (Acta neurochirurgica, 2012)
BACKGROUND: Aneurysm (AN) treatment appears to differ from country to country and even from centre to centre. Therefore we decided to conduct a survey in order to better understand the "state of the art" in aneurysm treatment in Europe. The primary aim was to understand the roles of clipping and coiling in aneurysm treatment. METHODS: An interactive form was sent to major European neurosurgical centres. The responses relating to AN location, status (ruptured/unruptured) and treatment modality were divided with regard to the volume of cases and the centre's geographical location. RESULTS: Responses were received from 96 European centres. The main finding was that clipping was used significantly more often in Eastern Europe than in the rest of Europe to treat ruptured ANs of the anterior circulation. Almost all ruptured ANs across all locations are treated actively. The treatment of unruptured aneurysms of the anterior circulation is similar. The median relating to observed unruptured ANs across the Europe was 10 %. Posterior circulation ANs are treated predominantly by coiling, regardless of aneurysm status or geographical location. The average number of coilers versus surgeons per centre was 2.5:3.0 in Western, 1.9:3.6 in Southern, 1.9:4.3 in Eastern and 2.7:3.1 in Northern Europe. CONCLUSIONS: The way in which intracranial aneurysms are treated appears to correlate with the economic development of European countries. It is probably also affected by the lack of experienced coilers in Eastern Europe.
Keywords: terapeutická embolizace; Endovascular Procedures; Surgical Instruments; Europe; endovaskulární výkony; výkony cévní chirurgie; výsledek terapie; průzkumy zdravotní péče; lidé; Evropa; východní Evropa; Intracranial Aneurysm; Treatment Outcome; Embolization, Therapeutic; Vascular Surgical Procedures; Brain Infarction; intrakraniální aneurysma; Europe, Eastern; Internet; mozkový infarkt; Developing Countries; rozvojové země; Health Care Surveys; internet; chirurgické nástroje; Humans